Stabilization of Hfq-mediated translational repression by the co-repressor Crc in Pseudomonas aeruginosa. Issue 12 (17th June 2021) - Malecka, Ewelina M; Bassani, Flavia; Dendooven, Tom; Sonnleitner, Elisabeth; Rozner, Marlena; Albanese, Tanino G; Resch, Armin; Luisi, Ben; Woodson, Sarah; Bläsi, Udo
Abstract: In Pseudomonas aeruginosa the RNA chaperone Hfq and the c atabolite r epression c ontrol protein (Crc) govern translation of numerous transcripts during carbon catabolite repression. Here, Crc was shown to enhance Hfq-mediated translational repression of several mRNAs. We have developed a single-molecule fluorescence assay to quantitatively assess the cooperation of Hfq and Crc to form a repressive complex on a RNA, encompassing the translation initiation region and the proximal coding sequence of the P. aeruginosa amiE gene. The presence of Crc did not change the amiE RNA-Hfq interaction lifetimes, whereas it changed the equilibrium towards more stable repressive complexes. This observation is in accord with Cryo-EM analyses, which showed an increased compactness of the repressive Hfq/Crc/RNA assemblies. These biophysical studies revealed how Crc protein kinetically stabilizes Hfq/RNA complexes, and how the two proteins together fold a large segment of the mRNA into a more compact translationally repressive structure. In fact, the presence of Crc resulted in stronger translational repression in vitro and in a significantly reduced half-life of the target amiE mRNA in vivo . Although Hfq is well-known to act with small regulatory RNAs, this study shows how Hfq can collaborate with another protein to down-regulate translation of mRNAs that become targets for the degradative machinery.